ECONOMIC AND ASYMMETRIC INFORMATION AS MODERATION VARIABLES, CREDIT RISKS, AND CREDIT PRICES - Masno Marjohan; Guruh Dwi Pratama (JURNAL DARMA AGUNG, 2023)
Profitability is the ability of an enterprise to make a profit in a certain period of time, a good and profitable enterprise is successful and in demand among shareholders. The purpose of this study is to determine the importance of asymmetric information, profitability, and the effect of credit risk on credit prices and profitability as limiting variables in the banking sector. This research covers all banking companies listed on the Indonesia Stock Exchange, as many as 33 banking companies. There are 8 banking companies whose research methods consist of hypothesis testing with multiple analysis techniques and absolute difference moderation testing. The results showed that changes in information asymmetry and profitability do not affect credit prices, credit risk affects credit prices (positive), and information asymmetry, credit risk, and profitability together affect credit prices (positive), profitability cannot limit (strengthen) credit prices. Asymmetry of information in credit prices. The sale of credit by banks is considered to contain risks. The greater the loan provided by the bank, the greater the credit risk of the bank. More research on credit pricing is needed. versatile and on a larger scale.